A cosmologia de Judá Abravanel (Leão Hebreu) - Martins, Daniel Rodrigues De Assis [UNIFESP] (2019)
This work is due to a reading of the Dialogues of Love of Judah Abravanel (Hebrew Lion) that seeks to interpret his philosophy by the cosmological bias. The work was written in Renaissance Italy of the sixteenth century and gained great popularity at the time. However, the author had his intellectual formation in the Iberian Peninsula, his birthplace. Knowing about the cultural wealth of the peninsula and its role in the transmission of Greek and medieval philosophy to Christian Europe, we are obliged to consider the philosopher’s roots as fundamental in the architecture of his work. This work aims at exposing the cosmic notion of Dialogues, seeking a perception about the great relevance of this notion to understanding the work. In addition, we also aspire to an interpretation of its cosmology as a direct inheritance of the Arab-Jewish world. This view is corroborated by Judah Abravanel's use of the emanationist system of Al-Farabi and Avicenna, one of the great gems developed by medieval philosophy written in Arabic.